(untitled) (Journal of Atomic and Molecular Sciences, 2018)
A quantum mechanical approach has been used to investigate the antioxidative mechanism for scavenging •OOH and •OH radicals using mangiferin in solution phase. Mangiferin is also used as a potent applicant for organic semiconductor. The charge-transport properties in mangiferin have been studied based on the first-principle DFT combined with the Marcus-Hush theory. Density functional theory (DFT) calculations at the B3LYP/6-311+G(d,p) level were used to optimize mangiferin and its different forms. The lowest theoretical bond dissociation enthalpy (BDE) value for 7-OH site of mangiferin in water, indicates that 7-OH group is important in the antioxidant activity. The relative values of enthalpies also show that oxidation of mangiferin by •OOH and •OH radical is an exothermic process. The predicted maximum electron mobility value of mangiferin is 0.148 cm² V^-1 s^-1, which appears at the orientation angle near 49°/311° of conducting channel on the reference planes ab. Theoretical investigation of natural semiconductors is helpful for designing higher performance electronic materials used in biochemical and industrial field to replace expensive and rare organic materials.